Estudo de ß-glucanas extraídas dos fungos Geastrum saccatum e Polyporos dermoporus: características químicas e atividades biológicas - Dore, Celina Maria Pinto Guerra (2006)
Fungal polysaccharides have received a great deal of attention due to itsbecause of their potential use in a wide rangegreat variety fromof industries. Some studies have demonstrated that polysaccharides extracted offrom basidiomycetes they have presented significant properties as anti-inflammatory, antimicrobial, antioxidant and anti-tumoral properties. In spite of thisDespite these potential properties, these mushrooms have not been insufficiently investigated, and the great number of antibiotics number produced forby these organisms suggests that they canmay be a new source of bioactives composites source. In tThe present work, reports onlated the chemical composition, potential antioxidant, antiinflammatory and citotoxycity of extracted polymers extracted offrom the fruits bodies of the fungiius Geastrum saccatum and Polyporus dermoporus, native mushrooms of the Atlantic forest inof the state of the Rio Grande do Norte, Brazil. The Cchemical analyses had revealed ademonstrated text of total sugar rates of 65% and 49%, and proteins of 7.0% for in extracts of G. saccatum and P. dermoporus extracts, respectively. The analyses ofNMR spectroscopy of RMN had demonstrated that these extracts are composites forof a complex involving β- glucans and- proteins complex. The inhibition of the formation of superoxide radicals formation was of 88.4% in G. saccatum and 83.3% in P. dermoporus, and 75 and 100% for inhibition of hydroxyls radicals inhibition. TopicalThe topic application of extracts the 10, 30 and 50 mg/kg extract in BALBc mice with cutaneous inflammation induced byfor croton oil demonstrated to inhibitedion of ear edema of ear and cells polimorfonuclears cells atin the inflamed siteplace, being this reply more effective in lower concentrations being more effective. The evaluation of the glucans of G. saccatum and P. dermoporus glucans under induced pleurisy for carrageenan-induced pleurisya of showed the antiinflammatory action of these composites., being analyzed tThe frame number in the pleural exudates and thedosage of nitric oxide dosage was also analyzed. The cytotoxic action of these polymers was analyzed throughthrough the mitochondrial function (MTT). The incubation of the glucans with mononuclear cells of the peripheral blood demonstrated that the extracted glucans extracted fromof G. saccatum havepossess a moderate cytotoxic action. These results suggest that these mushrooms possess polymers formed byfor a complex glucana-protein complex, with antiinflammatory and antioxidant actions